Performance measure of case based reasoning (CBR) for ammonia in water by specific concentration - Muhamad Faruqi, Zahari; Muhammad Sharfi, Najib; Suhaimi, Mohd Daud; Mujahid, Mohamad; Nur Farina, Hamidon Majid (2021)
Toxic gases are very common in industry which can be harmful to living species. This research purpose to monitoring and sustain environment and avoiding pollution and poisoning. The development on monitoring system for ammonia gases is crucial to avoid incident of poisonous air pollutants in commercialized industry. Hence, there is need to introduce simple air quality device to monitor the air pollution. Electronic Nose (E-Nose) is one of the device that can help to monitor this air pollution for the odor-profile gas that been harmful to living species. E-Nose is integrated with intelligent classification which is Case Based Reasoning (CBR) to enhanced the monitoring system. The experimental result shows E-nose that integrated with CBR was accomplished to classify data above than 70% of accuracy and nearly approach 80% of accuracy with 50% of Specificity and sensitivity.